The role of the hydrogen index of a local anesthetic solution in increasing the effectiveness of local anesthesia in dentistry (Эндодонтия Today, 2020)
The important characteristic of a local anesthetic solution is the value of the hydrogen index. The aim of the study was to determine the relationship between the value of the hydrogen index of a local anesthetic and the objective efficacy of local anesthesia. It is objectively shown that solutions of local anesthetics, whose pH level is weakly alkaline or greater than 4.9, take precedence in evaluating the effectiveness of local anesthesia. Subjectively, patients note the absence of pain during injection, as well as discomfort when opening the mouth in the case of conductive methods of anesthesia.